Masculinity and Femininity: A multidimensional approach - Menéndez Aller, Álvaro; Montes-Álvarez, Pelayo; Postigo, Álvaro; González-Nuevo, Covadonga; García-Fernández, Jaime; Cuesta, Marcelino; García-Cueto, Eduardo (Anales de Psicología / Annals of Psychology, 2022)
The research on Masculinity and Femininity has a long history. Despite this, there is still discussion about the nature of these concepts. In the present study, the development of the Oviedo Gender Roles Scale (GRSO) is presented. A sample of 612 participants belonging to general Spanish population is used (Myears = 34.2; SDyears = 15.9). The dimensionality, discrimination indices, reliability and evidence of convergent and divergent validity of the instrument were studied. In addition, differences in general (Big Five model) and specific personality traits based on sex were measured and an ANCOVA was performed controlling the variables of Masculinity and Femininity. A good fit to a three-factor multidimensional structure, with Cronbach’s alphas indicating good reliability (Socioemotional = .75; Comparison = .81; Aggressiveness = .77) and adequate evidence of validity were observed. Differences based on sex were observed in various personality traits, but when controlling for Masculinity and Femininity, such differences disappeared. ERGO is a reliable and valid test for the study of gender roles. The implication of a multidimensional approach on Masculinity and Femininity is discussed.